Philosophical Life dalam Pandangan Abu Bakr A-Razi: Philosophical Life dalam Pandangan Abu Bakr A-Razi - Syahuri Arsyi (STAI Al-Mujtama Pamekasan, 2025)
Abu Bakr al-Razi (863-935 A.D.) was a trusted classical thinker. His knowledge covers various disciplines, such as philosophy, medicine, physics, chemistry and others. In terms of theology, al-Razi is more inclined to Mu'tazilite theology. In philosophy many influenced Greek thought, especially Platonism. Unlike previous anti-platonic philosophers, al-Razi tried to harmonize rational philosophy. al-Razi's excellence in various fields of philosophy has not been much explored so that it becomes an addition to the Islamic scientific treasure. This paper seeks to explore ideas from Al-Razi's philosophy of life. The result of this study is that Al-Razi's philosophy of life is based on the guidance of rationality utilizing elements of the teachings of Platonism through spiritual medicine (spiritual physic).